Escalas de risco de Torrington e Henderson e de Epstein: aplicabilidade e efetividade nas ressecções pulmonares - Stanzani, Fabiana [UNIFESP] (2005)
OBJECTIVE: To compare the incidences of pulmonary and cardiopulmonary postoperative complications estimated using, respectively, the scoring systems devised by Torrington and Henderson and by Epstein in a populational sample undergoing lung resection for the treatment of lung cancer. METHODS: Prospective data from patients submitted to resection of one or more pulmonary lobes were selected from the databases of two tertiary-care hospitals. The outcome measures were pulmonary complications, cardiac complications and mortality rates. Fisher's exact test was used to evaluate the concordance between the predicted and observed complications. RESULTS: The Torrington and Henderson scoring system was applied to 50 patients, in which the risk was found to be mild in 12, moderate in 32, and high in 6. Although accurately identifying patients at high risk, the Torrington and Henderson scale underestimated the rate of postoperative cardiopulmonary complications in the mild and moderate risk categories (p = 0.0003 and p = 0.0006, respectively). The Epstein scoring system was applied to 38 patients, 4 of which were found to be at high risk, and 34 of which were found to be at mild risk. The Epstein scale also underestimated the risk in the patients (the majority) that were classified as being at mild risk (p < 0.0001) and yet, like the Torrington and Henderson scale, accurately identified those at high risk. CONCLUSION: Neither of the two scoring systems analyzed were found to be appropriate for predicting the risk of pulmonary and cardiopulmonary complications in most cases.